Synergistic thermal and surface area properties of Al2O3–TiO2/water hybrid nanofluids - Yokanan Gustino Djentoe; Farrel Yoga Widiasto; Hilbran Tama Dida Effendi; Musabbikhah; Sri Hartati; Budi Santoso; Budi Kristiawan; Agung Tri Wijayanta (Case Studies in Chemical and Environmental Engineering)
This work investigated experimentally on synergistic thermal and surface area properties of water-based Al2O3–TiO2 hybrid nanoparticles at a given volume ratio (50:50). Morphology and structure characterization were performed using Transmission Electron Microscope (TEM) and Surface Area Analysis (SAA), while thermal properties were analyzed using a thermal properties analyzer. The aims of this study were to investigate morphology and structure characterization and to evaluate thermal behavior using Transient Line Heat Source (TLHS), including thermal conductivity, heat capacity, and diffusivity. TEM micrographs revealed that TiO2 and Al2O3 nanoparticles were characterized by fractal-like arrangements and quasi-spherical morphology, respectively. The structural analysis of TiO2 and Al2O3 nanoparticles reveals a mesoporous structure with curve isotherm type IV that has loop hysteresis characteristics. The thermal durability of the water-based Al2O3–TiO2 hybrid nanoparticles is shown to have a strong relationship with the Moldoveanu model, confirming the trend of increasing thermal durability with a decrease in temperature as a result of increased nanoparticle mobility. According to this study, thermal behavior indicates that there are differences in temperature between 20 and 65 °C. Heat capacity increases significantly from 4 to 8 MJ/m2·K, with the fastest change occurring between 20 and 30 °C, whereas thermal diffusivity is bounded between 0 and 0.2 mm2/s. All of this highlights the potential applications in analysis and energy storage, highlighting the transfer characteristics of nanomaterials that are useful. The potential of hybrid nanofluids in long-term thermal management systems is demonstrated in this case study.